Dinâmica fitossociológica e de crescimento de um fragmento florestal manejado em 1993, no noroeste do RS - Vendruscolo, Rafael (2015)
After two decades of prohibition of native forests commercial harvest in Rio Grande do Sul, begins the first studies about the effect of Forest Management Plans (FMP). This work will show mainly what was the effect of FMP in natural forests and support the adjustment of the current legislation in favor of the forest sustainable use return. This work aims to analyze a forest located in the transition area between the Araucaria Forest and Deciduous Forest where was developed a FMP in 1993. The area of 52 hectare is located in the municipality of Herval Seco in the Northwest region of Rio Grande do Sul State, Brazil. Thus, we installed 31 forest inventory plots with 20 x 50 m in a systematic grid. At these plots were raised the diameter, morphological inversion point, commercial height, total height, quality, health and phytosociological position of all individuals with ≥ 10 cm in diameter at breast height (DBH), and was made the botanical identification at the level of family, genus and species. Were also collected core samples from trees with average DBH, maximum and minimum DBH of each plot. The growth of information was related to the climatic data obtained from the National Institute of Meteorology (INMET) and automatic station Frederico Westphaln, and in the database Agroclimatology Laboratory (Lagro). The results indicated the diversity of species in 2013 is higher than in 1993, today the area contains 81 species of 66 genera and 33 botanical families. The forest inventory of 2013 proposed the division of the area into two strata due to the large difference in the wood stock, with: Stratum 1 with 152 m³.ha-1 and stratum 2 with 43 m³.ha-1. None of the strata reached the 155 m³.ha-1, which should be the remaining stock after FMP in 1993. The Araucaria angustifolia, if considered as an isolated species, responded positively to the PMFS and increased both the number and the average volume of trees, when compared to 1993. The average annual increase in the last twenty years for Araucaria angustifolia was 0.81 cm, ranging from 0.26 cm to 1.39 cm. The annual growth rings of Araucaria angustifolia presented a linear correlation with the average annual temperature. The resulting equation was Inc = -0.09249 + 0,044913.Tmed with R² of 0.28, Syx of 5.42% and CV of 5.57%. In general the fragment didn´t recovered the wood stock of 1993, but increased its biodiversity. Considering single the Araucaria angustifolia the intervention was very favorable to it´s growth and perpetuation.